1994
DOI: 10.1002/jnr.490390602
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid regulates the development of oligodendrocyte precursor cells in vitro

Abstract: Cultures of oligodendrocyte precursor cells can be grown from brain hemispheres of newborn rats. These cells, also called O-2A progenitor cells, can differentiate in vitro into oligodendrocytes or type 2 astrocytes. Basic FGF and PDGF are known to stimulate their proliferation and delay their differentiation. Lack or excess of retinoic acid (RA) has been known for a long time to alter brain development suggesting that this compound is involved in normal brain development. Here we report that RA partially inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 110 publications
(130 reference statements)
1
46
0
Order By: Relevance
“…Consistent with previous reports (Barres et al, 1994;Laeng et al, 1994;Noll and Miller, 1994), we found that RA treatment promoted a more bipolar morphology in O-2A cells (data not shown). Additionally, under culture conditions that promoted lineage progression (N1, PDGF, or bFGF), treatment with 1 M RA significantly decreased the percentage of O-2A cells that developed into O4 ϩ pro-oligodendroblasts (Fig.…”
Section: Ra Reversibly Inhibits O-2a Cell Proliferation and Downregulsupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with previous reports (Barres et al, 1994;Laeng et al, 1994;Noll and Miller, 1994), we found that RA treatment promoted a more bipolar morphology in O-2A cells (data not shown). Additionally, under culture conditions that promoted lineage progression (N1, PDGF, or bFGF), treatment with 1 M RA significantly decreased the percentage of O-2A cells that developed into O4 ϩ pro-oligodendroblasts (Fig.…”
Section: Ra Reversibly Inhibits O-2a Cell Proliferation and Downregulsupporting
confidence: 93%
“…A, An increase in the sustained current density was observed after culture in 45 mM [K ϩ ] o for 48 hr (see also Aii, Summary histograms of data obtained at a test pulse of ϩ70 mV reveals an upregulation of both the current amplitude and the current density when normalized for any changes in membrane capacitance. Bi, Similarly, an upregulation of the Kir current density was also observed after chronic exposure to 45 mM [K ϩ ] o culturing conditions (Bi,1,3,4 ) (see also (Barres et al, 1994;Laeng et al, 1994;Noll and Miller, 1994). The effects of RA on cell proliferation appear to be attributable, at least in part, to its action on voltage-dependent K ϩ channels, because O-2A cells cultured in RA displayed a significant downregulation of both sustained and transient K ϩ currents.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Estradiol (40), retinoic acid (41), and thyroid hormone (14,21,42,43) have all been implicated in regulating the differentiation of glial cells in culture, suggesting an interaction of various hormones in the myelination process. Corticosteroids have played an important role in the diagnosis and therapy of demyelinating diseases (44)(45)(46) and have been found to modulate myelin proteins in oligodendrocytes (14,19).…”
Section: Discussionmentioning
confidence: 99%